Advance decision making – rhetoric or reality?. (2nd January 2018) - Johnston, Carolyn
Abstract : The Mental Capacity Act 2005 introduced a statutory framework for advance decisions, thus promoting autonomous healthcare decision making in advance of loss of capacity. In order to be valid and applicable, and so binding on healthcare professionals, advance decisions refusing treatment (ADRT) must specify treatments to be refused and the circumstances of refusal. Recent case-law indicates that a high level of specificity is required for advance refusals of life-sustaining treatment and, in contrast to a presumption of capacity for contemporaneous decisions, in some circumstances capacity must be demonstrated at the time of making the advance decision. In comparison with the 'stringent' requirements for ADRT, the more generic Advance Care Planning (ACP) is gaining more prominence in end of life decision making. The paper explores recent case-law and its impact on the effectiveness of ADRT in practice and compares with ACP.